Psycho-social, Criminological and Legal Aspects of Domestic Violence in Albania - Prifti, Aleks (2013)
Domestic violence is an acute social problem, because it affects society Bases its Foundations, Such as the family. It is not specific to Albania, but it is omnipresent and only its causes make it different. This article provides a latest Optics on psychosocial and criminological Aspects of the Phenomenon of Domestic Violence in Albania in the past 5 years. Through a comparative analysis of indicators of Domestic Violence crime in the country and the regional level, the aim is to provide its dynamics in the last 5 years and its development trends in this time period. The paper aims is to detect and pose Factors crime and psycho-social cause the generation and spread of this Phenomenon with great impact on the family environmentally, social and political development of the country. Paper Also Seeks to present the spread of forms of Domestic Violence, vulnerable groups from violence in the family; social and Cultural attitudes That Hinder the reporting of Domestic Violence In addition, the article analyzes the problems of Legislation, penal policy, Aspects of police preventive Social Measures Legislation and the Involvement of civil society actors in reducing this disturbing Phenomenon. Were obtained in the study of Certain Litigation Cases typically Analyze the existing problems in the field of conviction of several authors and especially to those repeaters. What GAPS and cracks no Legislation in this area and recommendations on how to Improve the Legislation in order to PREVENT this crime. Role of the State Police to provide services to address, investigate and reduce Cases of Domestic Violence, or its Coordination with other stakeholders for appropriate treatment of Domestic Violence Cases. Finally, the paper Aims to Assist in the development of Areas That May be impacted by the Program of the Government to Improve the Situation. The methodology: the paper was realized via a combined methodological approach with Statistical official date, Cases study, study of perpetrator's of Domestic Violence profile, phenomenology, social context, Keywords: Domestic Violence, criminological Factors, Family Environment, Reduction of Domestic Violence, Criminal policy